Lamin A/C facilitates DNA damage response by modulating ATM signaling and homologous recombination pathways - Seong-jung Kim; Su Hyung Park; Kyungjae Myung; Kyoo-young Lee (Animal Cells and Systems)
Lamin A/C, a core component of the nuclear lamina, forms a mesh-like structure beneath the inner nuclear membrane. While its structural role is well-studied, its involvement in DNA metabolism remains unclear. We conducted sequential protein fractionation to determine the subcellular localization of early DNA damage response (DDR) proteins. Our findings indicate that most DDR proteins, including ATM and the MRE11-RAD50-NBS1 (MRN) complex, are present in the nuclease – and high salt-resistant pellet fraction. Notably, ATM and MRN remain stably associated with these structures throughout the cell cycle, independent of ionizing radiation (IR)-induced DNA damage. Although Lamin A/C interacts with ATM and MRN, its depletion does not disrupt their association with nuclease-resistant structures. However, it impairs the IR-enhanced association of ATM with the nuclear matrix and ATM-mediated DDR signaling, as well as the interaction between ATM and MRN. This disruption impedes the recruitment of MRE11 to damaged DNA and the association of damaged DNA with the nuclear matrix. Additionally, Lamin A/C depletion results in reduced protein levels of CtIP and RAD51, which is mediated by transcriptional regulation. This, in turn, impairs the efficiency of homologous recombination (HR). Our findings indicate that Lamin A/C plays a pivotal role in DNA damage repair (DDR) by orchestrating ATM-mediated signaling, maintaining HR protein levels, and ensuring efficient DNA repair processes.